Patterns of the distribution of organic carbon by fractions of primary soil particles - Paz-Pellat, Fernando; Covaleda, Sara; Hidalgo-Moreno, Claudia; Matus, Francisco; Báez, Aurelio; Velázquez-Rodríguez, Alma S.; Etchevers-Barra, Jorge D. (REVISTA TERRA LATINOAMERICANA, 2022)
In order to analyze the dynamics of soil organic carbon (SOC) associated with changes in land use / vegetation and management practices, it is necessary to develop models that can be used predictively. A modeling approach is the distribution of SOC by physical fractions of the primary organomineral complexes (clays, silts and sands), using ultrasound soil dispersion techniques, where it is necessary to optimize the sonication energies to achieve complete soil dispersion. Under this consideration of complete dispersion, the COLPOS model and its hypothesis are discussed, as well as its possible extensions when considering the masses and enrichments of the physical fractions of the soil, in addition to the analysis of the relationships between these fractions. To analyze the patterns associated with the COLPOS model and its extensions, the available Mexican soil fractionations using ultrasound are analyzed, in addition to three databases of similar fractionations published in the literature. The results show that the COLPOS model can be parameterized according to the size and mass of the soil particles; although for the case of the masses some results are inconsistent. From the analysis of the organic carbon ratios between fractions for two different kinetics, the relationships show greater dispersion than for the case of only kinetic fractions.